2004
DOI: 10.1111/j.1741-6612.2004.00046.x
|View full text |Cite
|
Sign up to set email alerts
|

What hinders and what helps? Searching for solutions to mature aged unemployment and the residential aged care workforce crisis

Abstract: Objective:  This paper provides an overview of a research project that investigated strategies to address the workforce crisis currently threatening the provision of health and residential care services to Australia's rapidly ageing population. Underpinning this project's development was the need to understand why, in the face of high levels of sustained mature age unemployment (and under‐employment) and the urgent need for staff in residential and community aged care, mature aged people do not consider, or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…A number of studies have examined employers’ attitudes to baby boomers as employees. Unemployed baby boomers reportedly feel powerless and lack self‐confidence in job seeking because they believe that employers consider them to be in poorer health than younger employees and to lack recent work experience and information and communication technology skills [45,46]. Some research has confirmed these respondents’ beliefs [47].…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have examined employers’ attitudes to baby boomers as employees. Unemployed baby boomers reportedly feel powerless and lack self‐confidence in job seeking because they believe that employers consider them to be in poorer health than younger employees and to lack recent work experience and information and communication technology skills [45,46]. Some research has confirmed these respondents’ beliefs [47].…”
Section: Resultsmentioning
confidence: 99%
“…However, achieving significant increases to mature age participation rests considerably upon reducing the barriers to labour force participation that many older Australians face. Indeed, the barriers are complex and interrelated covering issues of age discrimination, difficulties re‐skilling and retraining, availability of flexible workplaces and practices and barriers due to poor health and caring responsibilities . The solution to these problems is also complex – covering not only labour market policies, but those pertaining to integrating care responsibilities with paid work, improved health care across the life course and removing work disincentives associated with Australia's welfare, tax and superannuation systems.…”
Section: Discussionmentioning
confidence: 99%
“…This area of research requires detailed, careful modelling. The ageing population may generate sectoral shifts in labour demand; the most obvious of which being for those in the health and caring sectors . The IGR projects an almost doubling of GDP per capita over a 40‐year time frame, which in itself will increase demand throughout the economy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, research by Price et al . () found that a highly structured and inflexible management style impacted negatively on care worker satisfaction. Studies by Beer et al .…”
mentioning
confidence: 99%